Efficient approach to electron-deficient 1,2,7,8-tetraazaperylene derivatives - Tang, Ruizhi; Zhang, Fan; Fu, Yubin; Xu, Qing; Wang, Xinyang; Zhuang, Xiaodong; Wu, Dongqing; Giannakopoulos, Angelos; Beljonne, David; Feng, Xinliang (Organic Letters, 2014)
Using an efficient synthetic strategy, a novel class of 1,2-diazineembedded perylenes, namely 1,2,7,8-tetraazaperylene derivatives, have been successfully synthesized. These molecules were fully characterized by X-ray diffraction analysis, optical spectroscopy, and electrochemistry. The low-lying lowest unoccupied molecular orbital (LUMO) level of these molecules suggests their potential as good electronic acceptors.
CRIS-Team Scopus Importer:2023-03-20